SISTEM INFORMASI JOB FAIR PADA DINAS SOSIAL TENAGA KERJA DAN TRANSMIGRASI KOTA PEKALONGAN BERBASIS WEB - Aslam Fatkhudin; Imam Rosyadi; Nur Hesti Sulistyowati (KH. A. Wahab Hasbullah University, 2015)
Inputting data processing in Social Service Man power and Transmigration Pekalongan still using semi-computerized system. Most of inputting data is still a general nature that have been using the computer, but do not take advantage of the presence of the computer to the fullest. Such as company data, the data Applicants, and job position data. These data are not yet well organized and processed so thatwould be a problem if managed manually, because in addition to high error rates, also takes a long time in the preparation of the report. To overcome these problems will require a system of Job Fair Information On Social Service Manpower and Transmigration Pekalongan Based WEB. This application is built using the waterfall method commonly used in the making of the application. There are several stages in the development of this application, the stage of analysis, design, coding, testing, and implementation. This application uses the system design Data Flow Diagram. While the coding phase, the application is built using the programming language PHP with MySQL database. With the application is expected Users can more easily enter the data in the applicant, company data and job position data, making it mor eeffective and efficient. keywords :Applicants; Companies;Job Fair